Quetiapine versus Haloperidol in Controlling Conversion Disorder Symptoms; a Randomized Clinical Trial - Ghanbarizadeh, Saeed Reza; Dinpanah, Hossein; Ghasemi, Reza; Salahshour, Yaser; Sardashti, Samaneh; Kamali, Mostafa; Khatibi, Seyed Reza (Archives of Academic Emergency Medicine, 2018)
Introduction: About 5% of visits to emergency departments are made up of conversion disorder cases. This study was designed with the aim of comparing the effectiveness of quetiapine and haloperidol in controlling conversion disorder symptoms. Methods: The present single-blind clinical trial has been performed on patients with conversion disorder (based on the DSM-IV definition) presenting to emergency department of 9-Day Hospital, Torbat Heydariyeh, Iran, from January 2017 until May 2018. Results: 73 patients were allocated to haloperidol and 71 to quetiapine group. Mean age of these patients was 32.03 ± 12.80 years (62.50% female). Two groups were similar regarding the baseline characteristics. Within 30 minutes, 90.41% of haloperidol cases and 91.55% of quetiapine cases were relieved (p=0.812). The most common side effects after 30 minutes were extrapyramidal symptoms (9.59%) in the haloperidol group and fatigue and sleepiness (7.04%) in the quetiapine group. Extrapyramidal symptoms was significantly higher than the quetiapine group (p=0.013). Conclusion: The results of the present study showed that although quetiapine and haloperidol have a similar effect in relieving the patients from conversion disorder symptoms, the prevalence of extrapyramidal symptoms is significantly lower in the group under treatment with quetiapine. Therefore, it seems that quetiapine is a safer drug compared to haloperidol.